Transitivity System in Narrative Texts for Junior High School - Mulyanti, Wida; Wati, Setyo (Jurnal Pendidikan Edutama, 2022)
Abstract: This study describes the transitivity system in narrative texts in Junior High School textbooks also explores how the understanding of process types in narratives informs pedagogical practices. The study was designed by employing qualitative descriptive method. The findings show that the most frequent process is material process, followed by relational process, mental process, verbal process, and existential process. The behavioral process is absent from all of the analyzed texts. The findings show that the texts are categorized into simple narratives. Thus, it can be concluded that the texts in the textbooks correspond to the stages of students’ intellectual development. However, grammatical errors are also found in the texts. It means that transitivity analysis does not only cover the experiential meaning of texts, more broadly than that, it can also analyze clauses grammatically and lexically in detail up to errors in the use of function words with evidence of asynchronous meaning in the transitivity system. Furthermore, the pedagogical implications of transitivity analysis are as follows: 1) leads students to acknowledge the author’s purpose, 2) provides teachers with many ideas for experiential probe questions that students can use when exploring clauses in a text, and 3) sharpening students’ critical thinking. Keyword: junior high school textbooks, transitivity system, narrative texts. Abstrak: Penelitian ini menganalisis sistem transitivitas dalam teks naratif pada buku teks Sekolah Menengah Pertama serta mengeksplorasi bagaimana pemahaman tentang jenis berimplikasi pada praktik pedagogis. Penelitian ini dirancang dengan menggunakan metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa proses yang paling sering terjadi adalah proses material, diikuti proses relasional, proses mental, proses verbal, dan proses eksistensial. Proses perilaku absen dari semua teks yang dianalisis. Temuan menunjukkan bahwa teks-teks tersebut dikategorikan kedalam jenis teks naratif sederhana. Maka, dapat disimpulkan bahwa teks-teks naratif dalam buku teks telah sesuai dengan tahapan perkembangan intelektual siswa. Namun, kesalahan tata bahasa juga ditemukan dalam teks-teks tersebut. Hal ini menunjukkan bahwa analisis transitivitas tidak hanya dapat menunjukkan makna eksperiensial dalam teks, lebih luas dari itu, klausa yang tata bahasa dan maknanya asinkron juga dapat diketahui. Selanjutnya, implikasi pedagogis dari analisis transitivitas adalah sebagai berikut: 1) mengarahkan siswa untuk mengetahui tujuan penulis, 2) menyediakan ide bagi guru dalam membuat pertanyaan penyelidikan yang dapat digunakan siswa ketika menganalisis klausa dalam suatu teks, dan 3) meningkatkan kemampuan berfikir kritis siswa. Kata kunci: Buku teks Sekolah Menengah Pertama, sistem transitivitas, teks naratif